2013
DOI: 10.1186/1471-2458-13-516
|View full text |Cite
|
Sign up to set email alerts
|

‘All those things together made me retire’: qualitative study on early retirement among Dutch employees

Abstract: BackgroundDue to the aging of the population and subsequent higher pressure on public finances, there is a need for employees in many European countries to extend their working lives. One way in which this can be achieved is by employees refraining from retiring early. Factors predicting early retirement have been identified in quantitative research, but little is known on why and how these factors influence early retirement. The present qualitative study investigated which non-health related factors influence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
72
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(86 citation statements)
references
References 21 publications
11
72
1
2
Order By: Relevance
“…A study including qualitative interview data on 30 Dutch employees aged 60-64 who retired early found that organizational change was frequently reported as reasons for early retirement (7). Employees in this study highlighted loss of motivation to continue working due to job routines undergoing continuous changes not perceived as necessary.…”
Section: Mechanismsmentioning
confidence: 71%
See 1 more Smart Citation
“…A study including qualitative interview data on 30 Dutch employees aged 60-64 who retired early found that organizational change was frequently reported as reasons for early retirement (7). Employees in this study highlighted loss of motivation to continue working due to job routines undergoing continuous changes not perceived as necessary.…”
Section: Mechanismsmentioning
confidence: 71%
“…A demanding physical work environment can cause employees to retire earlier, but several studies have also linked the psychosocial work environment to early retirement (7,10). Organizational changes causing job insecurity, like down-sizing, have been associated with adverse health outcomes and disability pension (11)(12)(13)(14)(15), but when focus is on voluntary retirement, even minor organizational changes may play a role.…”
mentioning
confidence: 99%
“…Future research on larger samples should take into account differences between reasons for exit from paid work, although this is often a multifactorial process. This was demonstrated in a recent qualitative study in which was shown that an interplay between factors that pushed towards early retirement (e.g., conflicts at work), and factors that attracted towards early retirement (e.g., wish to enjoy life) led to early retirement of older workers [50].…”
Section: Methodological Considerationsmentioning
confidence: 89%
“…We suggest that future research also pays attention to changes in the meaning of work during the life course, and especially in the phase near retirement. Related to this, it might be that pre-retirement anticipation is not characterized by changes in the motivation to work, but rather by changes in the motivation not to work, ie, to do things outside of work, such as enjoyable activities with a non-working spouse, or informal care of grandchildren, family members or friends with health problems (31). This also calls for further research.…”
Section: Discussionmentioning
confidence: 99%